(untitled) (Revista Nacional de Odontología, 2015)
In the society of the 21st century —focused on the social economic development— the continuous industrialization, mining and productive activities such as agriculture, turn out to be attractive options. However, in the development of these activities, the use and emission of some chemical products to the environment, including heavy metals, is pretty frequent. Small amounts of some heavy metals may be in the organism of the living beings. Some of these heavy metals may intervene in biochemical reactions, while other metals do not have biological use. For this reason, occupational and passive exposure to heavy metals in the environment, or coming from the food, most be regulated, as quantities higher than the ones deemed normal may result in certain illnesses. Controlling exposures to heavy metals include monitoring the levels in different biological matrixes such as blood, urine, saliva, hair and nails. Each one of these matrixes shall be indicated according to the exposure experienced by the individual; it will also offer some advantages and limitations. That is why this revision aims to inform about the effects resulting from the excessive levels of some heavy metals, and the usefulness of biological matrixes to determine such levels.